Investigating the Improvement of Decoding Abilities and Working Memory in Children with Incremental or Entity Personal Conceptions of Intelligence: Two Case Reports - Alesi, Marianna; Rappo, Gaetano; Pepi, Annamaria (Frontiers in Psychology, 2016)
One of the most significant current discussions has led to the hypothesis that domain-specific training programs alone are not enough to improve reading achievement or working memory abilities. Incremental or Entity personal conceptions of intelligence may be assumed to be an important prognostic factor to overcome domain-specific deficits. Specifically, incremental students tend to be more oriented toward change and autonomy and to adopt more efficacious strategies. This study aims at examining the efficacy of a multidimensional intervention program to improve decoding abilities and working memory. Participants were two children (M age = 10 yr.) with developmental dyslexia and different conceptions of intelligence. Children were tested on a whole battery of reading and spelling tests commonly used in the assessment of reading disabilities in Italy. Then, they were given a multimedia test to measure motivational factors such as conceptions of intelligence and achievement goals Children took part in the T.I.R.D. Multimedia Training for the Rehabilitation of Dyslexia (Rappo & Pepi, 2010) reinforced by specific units to improve verbal working memory for three months. This training consisted of specific tasks to rehabilitate both visual and phonological strategies (sound blending, word segmentation, alliteration test and rhyme test, letter recognition, digraph recognition, trigraph recognition and word recognition are samples of visual tasks) and verbal working memory (rapid words and non-words recognition). Posttest evaluations showed that the child holding the incremental theory of intelligence improved more than the child holding a static representation. On the whole this study highlights the importance of treatment programs in which account is taken of both specificity of deficits and motivational factors. There is a need to plan multifaceted intervention programs based on a transverse approach, looking at both cognitive and motivational factors.